Juvenile Delinquency and the Online Environment: A New Challenge to Society - Ciurea, Ștefan Tiberiu (Acta Universitatis Danubius. Juridica, 2025)
In the context of accelerated digitalization and the expansion of social networks, juvenile delinquency in the online environment has become an increasingly visible and complex phenomenon, raising major concerns among specialists in criminology, social psychology, and education. This study investigates contemporary manifestations of delinquent behaviors among adolescents in the virtual space, focusing on cyberbullying, child pornography, and cybercrime, highlighting both individual and contextual factors that facilitate the adoption of these deviant behaviors, as well as their impact on minors’ psycho-social development. Furthermore, the present research emphasizes the significant correlation between the lack of parental supervision, group influences, and prolonged exposure to violent or deviant digital content. In conclusion, the findings underline the necessity of developing tailored public policies and educational programs aimed at preventing the escalation of juvenile delinquent behaviors online and supporting the process of digital responsibility.